Ceramic core material, ceramic core as well as preparation method and application of ceramic core
By using core materials combined with electromelted white corundum powder, metal silicon powder and silicon nitride powder, silicon nitride powder, silicon nitride composite ceramic core is formed, and the high-temperature nitriding reaction sintering and high solubility characteristics are used to solve the problems of insufficient high-temperature strength, poor deformation resistance, poor thermal shock resistance and poor removal performance in single crystal hollow turbine blade manufacturing, and excellent high-temperature performance and good removal performance are achieved.
Patent Information
- Application Number
- CN202411891921.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing ceramic core materials have problems such as insufficient high-temperature strength, poor deformation resistance, poor thermal shock resistance and poor removal performance when manufacturing single crystal hollow turbine blades.
The core material of electromelting white corundum powder, metal silicon powder and silicon nitride powder is used to form a silicon nitride-combined aluminum oxide composite ceramic core after sintering through high-temperature nitride reaction, and the removal efficiency is improved by using the high solubility of silicon nitride during the removal process.
It achieves excellent high-temperature strength, high-temperature deformation resistance, thermal shock resistance and good removal performance of the ceramic core, meeting the manufacturing needs of single crystal hollow turbine blades.
Smart Images

Figure CN119657816A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of investment casting, and in particular to a ceramic core material, a ceramic core and a preparation method and application thereof. Background Art
[0002] The development of high-performance aviation, aerospace engines and industrial gas turbines requires the continuous increase of turbine inlet temperature, thus placing higher demands on the temperature bearing capacity of turbine blades. To this end, high-temperature alloy turbine blades have achieved a development from solid to hollow in terms of structure, and a leap from polycrystalline, directional solidification to single crystal in terms of solidification method. Near-net-shape investment casting technology is currently the main technology for manufacturing hollow turbine blades with complex inner cavity structures, and the preparation of high-performance ceramic core materials is the prerequisite for the realization of this technology.
[0003] At present, the ceramic cores commonly used for casting high-temperature alloy hollow blades at home and abroad are silicon oxide-based ceramic cores and aluminum oxide-based ceramic cores. Although silicon-based ceramic cores have many advantages such as low linear expansion coefficient, good thermal shock resistance, and good core removal performance, they have poor temperature resistance and are only suitable for casting equiaxed hollow blades with low casting temperatures. Although aluminum-based cores can withstand higher temperatures, due to their stable chemical properties and the difficulty of core removal, they are also difficult to promote and apply in the casting of single crystal hollow blades. The patent application with publication number CN112062547A records an aluminum oxide / aluminum nitride composite ceramic core, which uses the property of aluminum nitride being easily dissolved in alkali solution to improve the core removal rate. However, there are two problems with the composite ceramic core in practical applications: first, aluminum nitride easily reacts with water, which causes the composite ceramic core to be easily corroded by moisture in the air during the strengthening process, storage and use, resulting in reduced strength and even structural damage; second, aluminum nitride will oxidize to form aluminum oxide during the shell roasting process. The dense aluminum oxide formed on the surface prevents the alkaline solution from contacting aluminum nitride during the core removal process, resulting in difficulty in dissolving the ceramic core and a long core removal time. In summary, there is currently no ceramic core material that meets the manufacturing needs of single-crystal hollow turbine blades.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a ceramic core material, a ceramic core and a preparation method and application thereof. The ceramic core of the present invention has excellent high-temperature strength, high-temperature properties such as deformation resistance and thermal shock resistance, and has good removal performance, which solves the problems of poor removal performance of existing alumina-based ceramic cores.
[0006] In order to achieve the above-mentioned purpose of the present invention, the first aspect of the present invention provides a ceramic core material, including a core material and a plasticizer; the core material includes the following components by weight: 65 to 85 parts of fused white corundum powder, 5 to 25 parts of metallic silicon powder and 1 to 15 parts of silicon nitride powder.
[0007] In a specific embodiment of the present invention, the particle size of the fused white corundum powder is 1-75 μm. Further, the aluminum oxide content of the fused white corundum powder is greater than 99.5 wt%, and the sodium oxide content is less than 0.1 wt%.
[0008] In a specific embodiment of the present invention, the particle size of the metal silicon powder is 0.5-10 μm. Furthermore, the purity of the metal silicon powder is greater than 99.5 wt%.
[0009] In a specific embodiment of the present invention, the particle size of the silicon nitride powder is 0.5-20 μm. Furthermore, the silicon nitride content in the silicon nitride powder is greater than 99.5 wt%.
[0010] In a specific embodiment of the present invention, the amount of the plasticizer is 15wt% to 25wt% of the core material.
[0011] In a specific embodiment of the present invention, the plasticizer comprises the following components by mass percentage: 88% to 92% semi-refined paraffin, 7% to 9% beeswax and 1% to 3% polyethylene.
[0012] A second aspect of the present invention provides a ceramic core, which is made of the ceramic core material described in the first aspect.
[0013] The third aspect of the present invention provides a method for preparing a ceramic core, comprising the following steps: mixing a core material and a plasticizer to form a slurry, and pressing to obtain a green blank; degreasing and sintering the green blank to obtain a sintered body; and then strengthening the sintered body.
[0014] In a specific embodiment of the present invention, the degreasing includes: calcining and degreasing the green blank in an air atmosphere. Further, the calcining includes: keeping the temperature at 140±10°C for 1.5 to 2.5 hours, heating to 200±10°C for 1.5 to 2.5 hours, then heating to 300±10°C for 3.5 to 4.5 hours, then heating to 400±10°C for 3.5 to 4.5 hours, and cooling the furnace to room temperature.
[0015] In a specific embodiment of the present invention, the sintering includes: in a nitrogen-containing protective atmosphere, keeping warm at 300±10°C for 0.5 to 1.5 hours, heating to 600±10°C for 3.5 to 4.5 hours, then heating to 800±10°C for 0.5 to 1.5 hours, then heating to 1400±10°C for 5 to 7 hours, and cooling the furnace to room temperature.
[0016] In a specific embodiment of the present invention, the strengthening treatment comprises: immersing the sintered body in a first strengthening liquid and a second strengthening liquid in sequence;
[0017] The first strengthening liquid comprises the following components by mass percentage: 50% to 80% of tetraethyl orthosilicate, 0% to 30% of acidic silica sol and 18% to 22% of anhydrous ethanol;
[0018] The second strengthening liquid comprises the following components in percentage by mass: 45% to 80% of epoxy resin, 20% to 44% of acetone and 0% to 30% of polyamide.
[0019] The fourth aspect of the present invention provides the use of a ceramic core prepared by the preparation method of the third aspect in the manufacture of single crystal hollow turbine blades.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) In the ceramic core material of the present invention, the core material is compounded with a certain amount of fused corundum powder, metallic silicon powder and silicon nitride powder, and silicon nitride as the second phase is matched with the other components to give the ceramic core more excellent high temperature strength, deformation resistance, thermal shock resistance, etc.; and silicon nitride as the bonding phase of the ceramic core has high solubility in high concentration alkaline solution, which greatly improves the removal efficiency of the ceramic core;
[0022] (2) The ceramic core material of the present invention is used to obtain a silicon nitride combined with alumina composite ceramic core after high-temperature nitridation reaction sintering. This can not only improve the sintering performance of the ceramic core and reduce the sintering temperature and sintering cost, but also ensure the excellent high-temperature strength, high-temperature deformation resistance, thermal shock resistance and removal rate of the prepared ceramic core, thereby ensuring the casting success rate of single crystal hollow blades. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1A process flow chart of a ceramic core preparation method according to an embodiment of the present invention;
[0025] Figure 2 This is a microstructure diagram of the finished ceramic core obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] The pouring temperature of single crystal hollow turbine blades is generally between 1550 and 1650°C. At this temperature, the high temperature strength of the silicon-based ceramic core decreases significantly, the creep resistance becomes weak, and it is easy to react with the alloy solution. Therefore, the use of silicon-based ceramic cores to cast single crystal hollow blades is prone to problems such as core breakage, eccentricity, deformation, and chemical sand adhesion, resulting in a low blade qualification rate. Although the aluminum-based core can withstand the pouring temperature of the single crystal hollow turbine blade, it is limited by its poor removal rate, making it difficult to use in the manufacture of single crystal hollow turbine blades. Based on this, the present invention is committed to providing an alumina-based ceramic core with excellent high temperature strength, high temperature deformation resistance, thermal shock resistance, and good multi-effect performance to meet the manufacturing requirements of single crystal hollow turbine blades for aircraft engines and gas turbines.
[0028] The first aspect of the present invention provides a ceramic core material, including a core material and a plasticizer; the core material includes the following components by weight: 65-85 parts of fused white corundum powder, 5-25 parts of metallic silicon powder and 1-15 parts of silicon nitride powder.
[0029] The ceramic core material of the present invention uses fused white corundum powder as the main raw material, silicon nitride and metal silicon powder as additives, and after high-temperature nitridation reaction and sintering, a silicon nitride-bonded alumina composite ceramic core can be obtained. Among them, silicon powder provides a silicon source for the nitridation reaction, and the nitridation reaction occurs in a nitrogen atmosphere to form a silicon nitride bonding phase in situ, and the fused white corundum powder is bonded to ensure bonding uniformity and further improve strength and other properties.
[0030] Silicon nitride as the second phase cooperates with the other components to give the ceramic core better high-temperature strength, deformation resistance, thermal shock resistance, etc.; and, the ceramic core mainly generates strength by bonding the alumina particles with silicon nitride. Since silicon nitride has high solubility in high-concentration alkaline solutions (for example, >30wt% NaOH or KOH aqueous solutions), it will quickly disintegrate during the removal process due to the dissolution of the silicon nitride bonding phase, greatly improving the removal efficiency.
[0031] The amounts of the components in the core material of the ceramic core material of the present invention may be as follows:
[0032] The amount of fused white corundum powder can be 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts or a range consisting of any two of them; the amount of metallic silicon powder can be 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or a range consisting of any two of them; the amount of silicon nitride powder can be 1 part, 3 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts or a range consisting of any two of them; thereby taking into account the high temperature strength, deformation resistance, thermal shock resistance and removal performance of the ceramic core.
[0033] In a specific embodiment of the present invention, the core material comprises the following components by weight: 65-85 parts of fused white corundum powder, 10-20 parts of metal silicon powder and 5-15 parts of silicon nitride powder. Alternatively, the core material comprises the following components by weight: 75-85 parts of fused white corundum powder, 10-15 parts of metal silicon powder and 5-10 parts of silicon nitride powder.
[0034] In a specific embodiment of the present invention, the particle size of the fused white corundum powder is 1 to 75 μm, for example, 1 μm, 5 μm, 10 μm, 20 μm, 40 μm, 50 μm, 60 μm, 75 μm or any two thereof. Further, the aluminum oxide content of the fused white corundum powder is greater than 99.5 wt%, and the sodium oxide content is less than 0.1 wt%.
[0035] In a specific embodiment of the present invention, the particle size of the metal silicon powder is 0.5-10 μm, for example, 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm or any two thereof. Furthermore, the purity of the metal silicon powder is >99.5 wt%.
[0036] In a specific embodiment of the present invention, the particle size of the silicon nitride powder is 0.5-20 μm, for example, 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 10 μm or any two thereof. Further, the silicon nitride content in the silicon nitride powder is greater than 99.5 wt%.
[0037] In a specific embodiment of the present invention, the amount of plasticizer used is 15wt% to 25wt% of the core material, for example, 15wt%, 18wt%, 20wt%, 22wt%, 25wt% or any two thereof, thereby ensuring fluidity and formability, and avoiding excessive content leading to an increase in core porosity that affects high temperature flexural strength.
[0038] In a specific embodiment of the present invention, the plasticizer includes the following components by mass percentage: 88% to 92% of semi-refined paraffin, 7% to 9% of beeswax and 1% to 3% of polyethylene.
[0039] For example, in different embodiments, the amount of each component in the plasticizer can be as follows by mass percentage: the amount of semi-refined paraffin can be 88%, 89%, 90%, 91%, 92% or a range consisting of any two thereof; the amount of beeswax can be 7%, 7.5%, 8%, 8.5%, 9% or a range consisting of any two thereof; the amount of polyethylene can be 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two thereof, and the weight average molecular weight of polyethylene is 100,000 to 500,000. In the subsequent embodiments, polyethylene with a weight average molecular weight of about 200,000 is used as an example for explanation, but it is not limited to this. The plasticizers in the above proportions can enable the core powder to obtain rheological properties, and can be made into blanks with the shape of the target product by pressing and other methods.
[0040] A second aspect of the present invention provides a ceramic core, which is made from the ceramic core material of the first aspect.
[0041] The third aspect of the present invention provides a method for preparing a ceramic core, comprising the following steps: mixing a core material and a plasticizer to form a slurry, and pressing to obtain a green blank; degreasing and sintering the green blank to obtain a sintered body; and strengthening the sintered body.
[0042] In a specific embodiment of the present invention, the fused white corundum powder, metal silicon powder and silicon nitride powder in the core material are premixed, and then mixed with a plasticizer to form a slurry. Further, the premixing includes: mixing the fused white corundum powder, metal silicon powder and silicon nitride and ball milling them. During the ball milling, the material ball mass ratio is 1: (2-3), the rotation speed is 120-150rpm, and the ball milling time is 3-6h.
[0043] In a specific embodiment of the present invention, alumina balls are used in the ball milling process; among the alumina balls: alumina balls with a diameter of 5 mm account for 45wt% to 55wt%, alumina balls with a diameter of 3 mm account for 25wt% to 35wt%, and alumina balls with a diameter of 1 mm account for 15wt% to 25wt%.
[0044] In actual operation, the ball milling process can be carried out in a roller ball mill, but is not limited thereto.
[0045] In a specific embodiment of the present invention, the preparation of the slurry includes: adding the core material to a molten plasticizer at 80 to 140° C. in batches, and stirring for 30 to 60 minutes. For example, the core material can be added to the molten plasticizer in 2 to 4 times, and the specific number of times and the amount added each time can be conventionally adjusted according to actual conditions to ensure uniform mixing.
[0046] In a specific embodiment of the present invention, during pressing, the pressing temperature is 90-140°C, for example, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or any two of them, the pressing pressure is 1-5MPa, for example, 1MPa, 2MPa, 3MPa, 4MPa, 5MPa or any two of them, and the holding time is 15-40s, for example, 15s, 20s, 25s, 30s, 35s, 40s or any two of them. The pressing operation of the present invention can be performed on a hot die casting machine.
[0047] In a specific embodiment of the present invention, degreasing includes: roasting and degreasing the green blank in an air atmosphere. Further, roasting includes: keeping the temperature at 140±10°C for 1.5 to 2.5 hours, heating to 200±10°C for 1.5 to 2.5 hours, heating to 300±10°C for 3.5 to 4.5 hours, heating to 400±10°C for 3.5 to 4.5 hours, and cooling the furnace to room temperature.
[0048] Wherein, the heating rates from room temperature to 140±10°C, from 140±10°C to 200±10°C, from 200±10°C to 300±10°C, and from 300±10°C to 400±10°C are each independently selected from 0.4 to 0.6°C / min, such as 0.5°C / min.
[0049] In the roasting and degreasing process of the present invention, the green body is placed in alumina powder in a ceramic sagger and subjected to corresponding roasting treatment.
[0050] In a specific embodiment of the present invention, sintering includes: in a nitrogen-containing protective atmosphere, keeping warm at 300±10°C for 0.5 to 1.5 hours, heating to 600±10°C for 3.5 to 4.5 hours, then heating to 800±10°C for 0.5 to 1.5 hours, then heating to 1400±10°C for 5 to 7 hours, and cooling the furnace to room temperature.
[0051] The heating rate from room temperature to 300±10°C is 2-3°C / min, for example, 2.5°C / min; the heating rate from 300±10°C to 600±10°C is 0.4-0.6°C / min, for example, 0.5°C / min; the heating rate from 600±10°C to 800±10°C is 2-3°C / min, for example, 2.5°C / min; the heating rate from 800±10°C to 1400±10°C is 2-3°C / min, for example, 2.5°C / min. The sintering of the present invention can be carried out by placing the degreased ceramic sagger equipped with the core in a nitriding furnace under a nitrogen atmosphere.
[0052] In a specific embodiment of the present invention, the protective atmosphere comprises a nitrogen atmosphere.
[0053] In a specific embodiment of the present invention, the sintered body obtained after sintering is surface cleaned, dimensionally inspected, and then trimmed, and then subjected to subsequent strengthening treatment.
[0054] In a specific embodiment of the present invention, the strengthening treatment includes: immersing the sintered body in a first strengthening liquid and a second strengthening liquid in sequence;
[0055] The first strengthening liquid includes the following components by mass percentage: 50% to 80% of tetraethyl orthosilicate, 0% to 30% of acidic silica sol and 18% to 22% of anhydrous ethanol;
[0056] The second strengthening liquid comprises the following components in percentage by mass: 45% to 80% of epoxy resin, 20% to 44% of acetone and 0% to 30% of polyamide.
[0057] In a specific embodiment of the present invention, the first strengthening liquid includes the following components by mass percentage: 50% to 60% of tetraethyl orthosilicate, 22% to 28% of acidic silica sol and 18% to 22% of anhydrous ethanol;
[0058] The second strengthening liquid comprises the following components in percentage by mass: 45% to 55% of epoxy resin, 36% to 44% of acetone and 9% to 11% of polyamide.
[0059] In terms of mass percentage, the dosage of each component in the first strengthening solution can be as follows:
[0060] The amount of ethyl orthosilicate can be 50%, 52%, 55%, 58%, 60% or any two of them; the amount of acidic silica sol can be 22%, 24%, 25%, 26%, 28% or any two of them; the amount of anhydrous ethanol can be 18%, 19%, 20%, 21%, 22% or any two of them. In the acidic silica sol, the SiO2 content is 29wt% to 32wt%, and the pH value is 2.1 to 4.0.
[0061] Calculated by mass percentage, the dosage of each component in the second strengthening liquid can be as follows:
[0062] The amount of epoxy resin used can be 45%, 48%, 50%, 52%, 55% or a range consisting of any two thereof, and the epoxy resin includes but is not limited to bisphenol A epoxy resin E51; the amount of acetone used can be 36%, 38%, 40%, 42%, 44% or a range consisting of any two thereof; the amount of polyamide used can be 9.5%, 10%, 10.5%, 11% or a range consisting of any two thereof, and the weight average molecular weight of the polyamide is 600-1100.
[0063] By using the first strengthening liquid and the second strengthening liquid to strengthen the sintered body, the strengthening liquid has low viscosity and high permeability, and a better strengthening effect is achieved; specifically, high-temperature strengthening and low-temperature strengthening of the sintered body can be achieved, the core deflection can be reduced, the creep resistance can be increased, and the room temperature bending strength of the core can be increased.
[0064] In a specific embodiment of the present invention, the soaking treatment includes: soaking in the solution for 1 to 2 hours in a negative pressure environment, drying naturally for 20 to 30 hours after taking out, and then drying at 120±5° C. Under the above conditions, the strengthening liquid is helped to fully enter the core pores to ensure the strengthening effect.
[0065] In a specific embodiment of the present invention, the room temperature flexural strength of the prepared ceramic core is 35-50MPa, the high temperature flexural strength at 1550°C is 18-29MPa, the high temperature deflection at 1550°C is 0.2-0.4mm, the apparent porosity is 26%-37%, and the core removal rate reaches 100%.
[0066] Figure 1 A flow chart of the preparation process of a ceramic core provided in an embodiment of the present invention.
[0067] The fourth aspect of the present invention provides the use of the ceramic core prepared by the preparation method of the third aspect in the manufacture of single crystal hollow turbine blades. When the ceramic core of the present invention is used in the manufacture of single crystal hollow turbine blades, the casting success rate of the single crystal hollow turbine blades can be significantly improved.
[0068] Example 1
[0069] This embodiment provides a method for preparing a ceramic core, comprising the following steps:
[0070] (1) Prepare the core material premix:
[0071] Weigh 85 parts by weight of fused white corundum powder (alumina content is 99.85wt%, Na2O content is less than 0.1wt%, particle size distribution is 10-75μm), 10 parts of metal silicon powder (purity is greater than 99.5wt%, particle size distribution is 0.5-10μm), and 5 parts of silicon nitride powder (purity is greater than 99.5wt%, particle size distribution is 0.5-20μm) for use. Put 200 parts by weight of alumina balls into a polytetrafluoroethylene ball mill, in which the balls with a diameter of 5mm account for 50wt%, the balls with a diameter of 3mm account for 30wt%, and the balls with a diameter of 1mm account for 20wt%; then put all the weighed core material powder into the ball mill, close the mouth of the jar and place it on a roller ball mill, turn on the ball mill, adjust the speed to 120rpm, and keep it for 3h. After the ball milling is completed, open the ball mill, pour the balls into the material tray, clean out the alumina balls, and obtain the core material premix.
[0072] (2) Preparation of ceramic core slurry:
[0073] Weigh 100 parts by weight of the core material premix and 20 parts by weight of the plasticizer, add the plasticizer into a heated stirring pot, heat to 120°C and keep warm, turn on the stirrer after the plasticizer melts, slowly add the core material premix in two batches, continue stirring for 60 minutes after the addition is completed, and obtain a ceramic core slurry. The plasticizer includes 90% semi-refined paraffin wax, 8% beeswax and 2% polyethylene by mass percentage.
[0074] (3) Pressing the green billet:
[0075] The slurry obtained in step (2) is heated to 120°C under vacuum and stirred for 30 minutes, and then the slurry is transferred to a hot die casting machine for pressing to obtain a blank; wherein the pressing temperature is 120°C, the pressing pressure is 3 MPa, and the holding time is 20 seconds.
[0076] (4) Degreasing:
[0077] The green blank is placed in the alumina powder of the ceramic sagger, and then the ceramic sagger containing the green blank is loaded into the degreasing furnace, and is roasted and degreased in an air atmosphere. The roasting and degreasing temperature regime is as follows: heating from room temperature to 140°C at a heating rate of 0.5°C / min, and keeping warm for 2 hours; then heating from 140°C to 200°C at a heating rate of 0.5°C / min, and keeping warm for 2 hours; then heating from 200°C to 300°C at a heating rate of 0.5°C / min, and keeping warm for 4 hours; then heating from 300°C to 400°C at a heating rate of 0.5°C / min, and keeping warm for 4 hours; cooling to room temperature with the furnace to obtain a degreased core.
[0078] (5) Sintering:
[0079] Place the degreased ceramic sagger with the core in the nitriding furnace, close the furnace door and evacuate to 10-1 Pa or more, then fill with nitrogen, start the electric furnace for nitriding sintering; the sintering temperature system is: heat up from room temperature to 300℃ at a heating rate of 2.5℃ / min, and keep warm for 1h; then heat up from 300℃ to 600℃ at a heating rate of 0.5℃ / min, and keep warm for 4h; then heat up from 600℃ to 800℃ at a heating rate of 2.5℃ / min, and keep warm for 1h; then heat up from 800℃ to 1400℃ at a heating rate of 2.5℃ / min, and keep warm for 6h; cool to room temperature with the furnace to obtain a core sintered body.
[0080] After the core sintered body is taken out of the furnace, it is taken out from the ceramic sagger, the surface is cleaned by blowing powder, and the shape is repaired after the size inspection.
[0081] (6) Strengthening:
[0082] The core sintered body is first subjected to high temperature strengthening, and then to low temperature strengthening. The high temperature strengthening process is as follows: the core sintered body is immersed in a container filled with high temperature strengthening liquid, and the container is placed in a low pressure vacuum box with an air pressure lower than atmospheric pressure (such as an air pressure of 0.08MPa), and immersed for 1 hour, so that the strengthening liquid fully enters the core pores, and is taken out and placed in a material tray for natural drying for 24 hours, and the naturally dried core is placed in a 120°C oven to dry, and a high temperature strengthened core is obtained. The low temperature strengthening process is as follows: the high temperature strengthened core is immersed in a container filled with low temperature strengthening liquid, and the container is placed in a low pressure vacuum box with an air pressure lower than atmospheric pressure (such as an air pressure of 0.08MPa), and immersed for 1 hour, so that the strengthening liquid fully enters the core pores, and is taken out and placed in a material tray for natural drying for 24 hours, and the naturally dried core is placed in a 120°C oven to dry, and a ceramic core product is obtained.
[0083] The high temperature strengthening liquid is prepared by mixing 55% of tetraethyl orthosilicate, 25% of acidic silica sol and 20% of anhydrous ethanol by mass percentage; the content of SiO2 in the acidic silica sol is 30wt% to 31wt%, and the pH value is 2.1 to 2.5. The low temperature strengthening liquid is prepared by mixing 50% of epoxy resin, 40% of acetone and 10% of polyamide by mass percentage. The epoxy resin is bisphenol A type epoxy resin E51, and the polyamide is 650 low molecular weight polyamide.
[0084] The microstructure of the ceramic core product obtained in this embodiment is shown in FIG. Figure 2 shown.
[0085] Example 2
[0086] This embodiment provides a method for preparing a ceramic core, comprising the following steps:
[0087] (1) Prepare the core material premix:
[0088] Weigh 75 parts by weight of fused white corundum powder (alumina content is 99.85wt%, Na2O content is less than 0.1wt%, particle size distribution is 10-75μm), 15 parts of metal silicon powder (purity is greater than 99.5wt%, particle size distribution is 0.5-10μm), and 10 parts of silicon nitride powder (purity is greater than 99.5wt%, particle size distribution is 0.5-20μm) for use. Put 200 parts by weight of alumina balls into a polytetrafluoroethylene ball mill, in which the balls with a diameter of 5mm account for 50wt%, the balls with a diameter of 3mm account for 30wt%, and the balls with a diameter of 1mm account for 20wt%; then put all the weighed core material powder into the ball mill, close the mouth of the jar and place it on a roller ball mill, turn on the ball mill, adjust the speed to 120rpm, and keep it for 3h. After the ball milling is completed, open the ball mill, pour the balls into the material tray, clean out the alumina balls, and obtain the core material premix.
[0089] (2) Preparation of ceramic core slurry:
[0090] Weigh 100 parts by weight of the core material premix and 15 parts by weight of the plasticizer, add the plasticizer into a heated stirring pot, heat to 140°C and keep warm, turn on the stirrer after the plasticizer melts, slowly add the core material premix in two batches, continue stirring for 45 minutes after the addition is completed, and obtain a ceramic core slurry. The plasticizer includes 90% semi-refined paraffin wax, 8% beeswax and 2% polyethylene by mass percentage.
[0091] (3) Pressing the green billet:
[0092] The slurry obtained in step (2) is heated to 120°C under vacuum and stirred for 30 minutes, and then the slurry is transferred to a hot die casting machine for pressing to obtain a blank; wherein the pressing temperature is 120°C, the pressing pressure is 4 MPa, and the holding time is 40 seconds.
[0093] (4) Degreasing:
[0094] The green blank is placed in the alumina powder of the ceramic sagger, and then the ceramic sagger containing the green blank is loaded into the degreasing furnace, and is roasted and degreased in an air atmosphere. The roasting and degreasing temperature regime is as follows: heating from room temperature to 140°C at a heating rate of 0.5°C / min, and keeping warm for 2 hours; then heating from 140°C to 200°C at a heating rate of 0.5°C / min, and keeping warm for 2 hours; then heating from 200°C to 300°C at a heating rate of 0.5°C / min, and keeping warm for 4 hours; then heating from 300°C to 400°C at a heating rate of 0.5°C / min, and keeping warm for 4 hours; cooling to room temperature with the furnace to obtain a degreased core.
[0095] (5) Sintering:
[0096] Place the degreased ceramic sagger with the core in the nitriding furnace, close the furnace door and evacuate to 10-1 Pa or more, then fill with nitrogen, start the electric furnace for nitriding sintering; the sintering temperature system is: heat up from room temperature to 300℃ at a heating rate of 2.5℃ / min, and keep warm for 1h; then heat up from 300℃ to 600℃ at a heating rate of 0.5℃ / min, and keep warm for 4h; then heat up from 600℃ to 800℃ at a heating rate of 2.5℃ / min, and keep warm for 1h; then heat up from 800℃ to 1400℃ at a heating rate of 2.5℃ / min, and keep warm for 6h; cool to room temperature with the furnace to obtain a core sintered body.
[0097] After the core sintered body is taken out of the furnace, it is taken out from the ceramic sagger, the surface is cleaned by blowing powder, and the shape is repaired after the size inspection.
[0098] (6) Strengthening:
[0099] The core sintered body is first subjected to high temperature strengthening, and then to low temperature strengthening. The high temperature strengthening process is as follows: the core sintered body is immersed in a container filled with high temperature strengthening liquid, and the container is placed in a low pressure vacuum box with an air pressure lower than atmospheric pressure (such as an air pressure of 0.08MPa), and immersed for 2 hours to allow the strengthening liquid to fully enter the core pores, and then take it out and place it in the material tray to dry naturally for 24 hours, and then place the naturally dried core in a 120℃ oven to dry, and obtain a high temperature strengthened core. The low temperature strengthening process is as follows: the high temperature strengthened core is immersed in a container filled with low temperature strengthening liquid, and the container is placed in a low pressure vacuum box with an air pressure lower than atmospheric pressure (such as an air pressure of 0.08MPa), and immersed for 2 hours to allow the strengthening liquid to fully enter the core pores, and then take it out and place it in the material tray to dry naturally for 24 hours, and then place the naturally dried core in a 120℃ oven to dry, and obtain a ceramic core product.
[0100] The high temperature strengthening liquid is prepared by mixing 55% of tetraethyl orthosilicate, 25% of acidic silica sol and 20% of anhydrous ethanol by mass percentage. The low temperature strengthening liquid is prepared by mixing 50% of epoxy resin, 40% of acetone and 10% of polyamide by mass percentage. The acidic silica sol, epoxy resin and polyamide are the same as those in Example 1.
[0101] Example 3
[0102] This embodiment provides a method for preparing a ceramic core, comprising the following steps:
[0103] (1) Prepare the core material premix:
[0104] Weigh 65 parts by weight of fused white corundum powder (alumina content is 99.85wt%, Na2O content is less than 0.1wt%, particle size distribution is 10-75μm), 20 parts of metal silicon powder (purity is greater than 99.5wt%, particle size distribution is 0.5-10μm), and 15 parts of silicon nitride powder (purity is greater than 99.5wt%, particle size distribution is 0.5-20μm) for use. Put 200 parts by weight of alumina balls into a polytetrafluoroethylene ball mill, in which the balls with a diameter of 5mm account for 50wt%, the balls with a diameter of 3mm account for 30wt%, and the balls with a diameter of 1mm account for 20wt%; then put all the weighed core material powder into the ball mill, close the mouth of the jar and place it on a roller ball mill, turn on the ball mill, adjust the speed to 120rpm, and keep it for 3h. After the ball milling is completed, open the ball mill, pour the balls into the material tray, clean out the alumina balls, and obtain the core material premix.
[0105] (2) Preparation of ceramic core slurry:
[0106] Weigh 100 parts by weight of the core material premix and 25 parts by weight of the plasticizer, add the plasticizer into a heated stirring pot, heat to 140°C and keep warm, turn on the stirrer after the plasticizer melts, slowly add the core material premix in two batches, continue stirring for 30 minutes after the addition is completed, and obtain a ceramic core slurry. The plasticizer includes 90% semi-refined paraffin wax, 8% beeswax and 2% polyethylene by mass percentage.
[0107] (3) Pressing the green billet:
[0108] The slurry obtained in step (2) is heated to 120°C under vacuum and stirred for 30 minutes, and then the slurry is transferred to a hot die casting machine for pressing to obtain a blank; wherein the pressing temperature is 120°C, the pressing pressure is 2 MPa, and the holding time is 10 seconds.
[0109] (4) Degreasing:
[0110] The green blank is placed in the alumina powder of the ceramic sagger, and then the ceramic sagger containing the green blank is loaded into the degreasing furnace, and is roasted and degreased in an air atmosphere. The roasting and degreasing temperature regime is as follows: heating from room temperature to 140°C at a heating rate of 0.5°C / min, and keeping warm for 2 hours; then heating from 140°C to 200°C at a heating rate of 0.5°C / min, and keeping warm for 2 hours; then heating from 200°C to 300°C at a heating rate of 0.5°C / min, and keeping warm for 4 hours; then heating from 300°C to 400°C at a heating rate of 0.5°C / min, and keeping warm for 4 hours; cooling to room temperature with the furnace to obtain a degreased core.
[0111] (5) Sintering:
[0112] Place the degreased ceramic sagger with the core in the nitriding furnace, close the furnace door and evacuate to 10-1 Pa or more, then fill with nitrogen, start the electric furnace for nitriding sintering; the sintering temperature system is: heat up from room temperature to 300℃ at a heating rate of 2.5℃ / min, and keep warm for 1h; then heat up from 300℃ to 600℃ at a heating rate of 0.5℃ / min, and keep warm for 4h; then heat up from 600℃ to 800℃ at a heating rate of 2.5℃ / min, and keep warm for 1h; then heat up from 800℃ to 1400℃ at a heating rate of 2.5℃ / min, and keep warm for 6h; cool to room temperature with the furnace to obtain a core sintered body.
[0113] After the core sintered body is taken out of the furnace, it is taken out from the ceramic sagger, the surface is cleaned by blowing powder, and the shape is repaired after the size inspection.
[0114] (6) Strengthening:
[0115] The core sintered body is first subjected to high temperature strengthening, and then to low temperature strengthening. The high temperature strengthening process is as follows: the core sintered body is immersed in a container filled with high temperature strengthening liquid, and the container is placed in a low pressure vacuum box with an air pressure lower than atmospheric pressure (such as an air pressure of 0.08MPa), and immersed for 1 hour, so that the strengthening liquid fully enters the core pores, and is taken out and placed in a material tray for natural drying for 24 hours, and the naturally dried core is placed in a 120°C oven to dry, and a high temperature strengthened core is obtained. The low temperature strengthening process is as follows: the high temperature strengthened core is immersed in a container filled with low temperature strengthening liquid, and the container is placed in a low pressure vacuum box with an air pressure lower than atmospheric pressure (such as an air pressure of 0.08MPa), and immersed for 1 hour, so that the strengthening liquid fully enters the core pores, and is taken out and placed in a material tray for natural drying for 24 hours, and the naturally dried core is placed in a 120°C oven to dry, and a ceramic core product is obtained.
[0116] The high temperature strengthening liquid is prepared by mixing 55% of tetraethyl orthosilicate, 25% of acidic silica sol (same as in Example 1) and 20% of anhydrous ethanol by mass percentage. The low temperature strengthening liquid is prepared by mixing 50% of epoxy resin, 40% of acetone and 10% of polyamide by mass percentage. The acidic silica sol, epoxy resin and polyamide are the same as in Example 1.
[0117] Example 4
[0118] This embodiment refers to the method for preparing the ceramic core of Embodiment 1, with the only difference being that in the sintering of step (4), the sintering temperature regime is different.
[0119] The sintering temperature regime of this embodiment is as follows: heating from room temperature to 300°C at a heating rate of 2.5°C / min, and keeping warm for 1 hour; then heating from 300°C to 600°C at a heating rate of 0.5°C / min, and keeping warm for 4 hours; then heating from 600°C to 1400°C at a heating rate of 2.5°C / min, and keeping warm for 4 hours; cooling to room temperature with the furnace to obtain a core sintered body.
[0120] Example 5
[0121] This embodiment refers to the method for preparing the ceramic core of Embodiment 1, with the only difference being that in the strengthening step (6), the composition of the strengthening liquid is different.
[0122] The strengthening liquid of this embodiment is composed of: the high temperature strengthening liquid is prepared by mixing 60% of tetraethyl orthosilicate, 22% of acidic silica sol and 18% of anhydrous ethanol by mass percentage. The low temperature strengthening liquid is prepared by mixing 55% of epoxy resin, 36% of acetone and 9% of polyamide by mass percentage. The acidic silica sol, epoxy resin and polyamide are the same as those in Example 1.
[0123] Example 6
[0124] This embodiment refers to the method for preparing the ceramic core of Embodiment 1, with the only difference being that in the strengthening in step (6), the composition of the strengthening liquid is different and is a conventional strengthening liquid.
[0125] The strengthening liquid of this embodiment is composed of: the high temperature strengthening liquid is prepared by mixing 80% of tetraethyl orthosilicate and 20% of anhydrous ethanol by mass percentage; the low temperature strengthening liquid is prepared by mixing 80% of epoxy resin and 20% of acetone by mass percentage. The epoxy resin is the same as in embodiment 1.
[0126] Comparative Example 1
[0127] Comparative Example 1 refers to the method for preparing the ceramic core of Example 1, except that the core material in step (1) is different.
[0128] The method for preparing the core material premix of comparative example 1 comprises: weighing 95 parts by weight of fused white corundum powder (alumina content is 99.85wt%, Na2O content is less than 0.1wt%, and particle size distribution is 10-75μm) and 5 parts of quartz glass powder (purity is greater than 99.9wt%, and particle size distribution is 0.5-20μm) for use. 200 parts by weight of alumina balls are loaded into a polytetrafluoroethylene ball mill, wherein the alumina balls have a diameter of 5mm and a proportion of 50wt%, the alumina balls have a diameter of 3mm and a proportion of 30wt%, and the alumina balls have a diameter of 1mm and a proportion of 20wt%; then all the weighed core material powder is loaded into the ball mill, the mouth of the mill is closed, and the core material premix is placed on a roller ball mill, the ball mill is turned on, the speed is adjusted to 120rpm, and maintained for 3h. After the ball milling is completed, the ball mill is turned on, the material balls are poured out into the material tray, and the alumina balls are cleaned out to obtain the core material premix.
[0129] Comparative Example 2
[0130] Comparative Example 2 refers to the method for preparing the ceramic core of Example 1, except that the core material in step (1) is different, the degreasing system in step (4) and the sintering system in step (5) are different.
[0131] The method for preparing the core material premix of comparative example 2 comprises: weighing 80 parts by weight of fused white corundum powder (alumina content is 99.85wt%, Na2O content is less than 0.1wt%, and particle size distribution is 10-75μm) and 20 parts of aluminum nitride powder (purity is greater than 99.9wt%, and particle size distribution is 0.5-30μm) for standby use. 200 parts by weight of alumina balls are loaded into a polytetrafluoroethylene ball mill, wherein the alumina balls have a diameter of 5mm and a diameter of 3mm, respectively, and the alumina balls have a diameter of 30wt%, respectively, and respectively, respectively, and the alumina balls have a diameter of 1mm and a diameter of 20wt%. Then, all the weighed core material powder is loaded into the ball mill, the mouth of the ball mill is closed, and the ball mill is placed on a roller ball mill, the ball mill is turned on, the speed is adjusted to 120rpm, and the ball mill is kept for 3h. After the ball milling is completed, the ball mill is turned on, the material balls are poured out to the material tray, and the alumina balls are cleaned out to obtain the core material premix.
[0132] The degreasing system of comparative example 2 includes: placing the green blank in alumina powder in a ceramic sagger, then loading the ceramic sagger containing the green blank into a degreasing furnace, and calcining and degreasing in an air atmosphere. The calcining and degreasing temperature system is: heating from room temperature to 140°C at a heating rate of 0.5°C / min, and keeping warm for 2h; then heating from 140°C to 200°C at a heating rate of 0.5°C / min, and keeping warm for 2h; then heating from 200°C to 300°C at a heating rate of 0.5°C / min, and keeping warm for 2h; then heating from 300°C to 600°C at a heating rate of 0.5°C / min, and keeping warm for 6h; cooling to room temperature with the furnace to obtain a degreased core.
[0133] The sintering system of Comparative Example 2 includes: placing the degreased ceramic sagger with the core in a nitriding furnace, closing the furnace door and evacuating to 10 -1 Pa or above, then fill with nitrogen, turn on the electric furnace for nitriding sintering; the sintering temperature system is: heat up from room temperature to 800℃ at a heating rate of 2.5℃ / min, and keep warm for 1h; then heat up from 800℃ to 1450℃ at a heating rate of 2.5℃ / min, and keep warm for 6h; cool to room temperature with the furnace to obtain a core sintered body.
[0134] After the core sintered body is taken out of the furnace, it is taken out from the ceramic sagger, the surface is cleaned by blowing powder, and the shape is repaired after the size inspection.
[0135] Experimental example
[0136] The room temperature flexural strength, 1550°C high temperature flexural strength, 1550°C high temperature deflection, apparent porosity, and core removal rate of the ceramic cores of different embodiments and comparative examples were tested. The test results are shown in Table 1.
[0137] The core removal rate refers to the core removal rate obtained by performing a core removal test at 3.0 MPa and 300° C. for 6 hours in a core removal kettle using 70 wt % KOH aqueous solution as the core removal liquid.
[0138] Table 1 Test results of different ceramic cores
[0139]
[0140]
[0141] It can be seen from the above test results that the ceramic core made using the ceramic core material of the present invention has excellent room temperature strength, high temperature strength, and high temperature deflection, and also has the advantages of low sintering temperature and easy removal, and can be used for the manufacture of single crystal hollow turbine blades.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. Ceramic core material, characterized in that: It comprises a core material and a plasticizer; the core material comprises the following components by weight: 65-85 parts of fused white corundum powder, 5-25 parts of metallic silicon powder and 1-15 parts of silicon nitride powder.
2. The ceramic core material according to claim 1, characterized in that: The core material comprises the following components by weight: 65-85 parts of fused white corundum powder, 10-20 parts of metallic silicon powder and 5-15 parts of silicon nitride powder.
3. The ceramic core material according to claim 1, characterized in that: Having at least one of the following characteristics: (1) The particle size of the fused white corundum powder is 1 to 75 μm; (2) The aluminum oxide content of the fused white corundum powder is greater than 99.5wt%, and the sodium oxide content is less than 0.1wt%; (3) The particle size of the metallic silicon powder is 0.5 to 10 μm; (4) The purity of the metallic silicon powder is greater than 99.5 wt %; (5) The particle size of the silicon nitride powder is 0.5 to 20 μm; (6) The silicon nitride powder has a silicon nitride content of >99.5 wt%.
4. The ceramic core material according to claim 1, characterized in that: The amount of the plasticizer is 15wt% to 25wt% of the core material; Preferably, the plasticizer comprises the following components by mass percentage: 88% to 92% semi-refined paraffin, 7% to 9% beeswax and 1% to 3% polyethylene.
5. A ceramic core, characterized in that: It is made from the ceramic core material described in any one of claims 1 to 4.
6. The method for preparing the ceramic core according to claim 5, characterized in that: The method comprises the following steps: mixing the core material and the plasticizer to form slurry, and pressing to obtain a green blank; degreasing and sintering the green blank to obtain a sintered body; and strengthening the sintered body.
7. The preparation method according to claim 6, characterized in that: The degreasing comprises: calcining and degreasing the green blank in an air atmosphere; Preferably, the calcination comprises: keeping warm at 140±10°C for 1.5 to 2.5 hours, heating to 200±10°C for 1.5 to 2.5 hours, heating to 300±10°C for 3.5 to 4.5 hours, heating to 400±10°C for 3.5 to 4.5 hours, and cooling the furnace to room temperature.
8. The preparation method according to claim 6, characterized in that: The sintering comprises: in a nitrogen-containing protective atmosphere, heat-treating at 300±10°C for 0.5-1.5h, heating to 600±10°C for 3.5-4.5h, heating to 800±10°C for 0.5-1.5h, heating to 1400±10°C for 5-7h, and cooling the furnace to room temperature.
9. The preparation method according to claim 6, characterized in that: The strengthening treatment comprises: immersing the sintered body in a first strengthening liquid and a second strengthening liquid in sequence; The first strengthening liquid comprises the following components by mass percentage: 50% to 80% of tetraethyl orthosilicate, 0% to 30% of acidic silica sol and 18% to 22% of anhydrous ethanol; The second strengthening liquid comprises the following components in percentage by mass: 45% to 80% of epoxy resin, 20% to 44% of acetone and 0% to 30% of polyamide.
10. Use of the ceramic core according to claim 5 or the ceramic core prepared by the preparation method according to any one of claims 6 to 9 in the manufacture of single crystal hollow turbine blades.
Citation Information
Patent Citations
Aluminum nitride / aluminum oxide composite ceramic core and preparation method thereof
CN112062547A